Burnout and Mental Health Challenges among Healthcare Providers - Mesfer S. Al-Qhtani; Sajdi S. Al-Mutairi; Ayed A. Al-Zahrani; Hasher A. Al-Otaibi; Faisal N. Al-Otaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Burnout among healthcare providers is acritical concern, characterized by emotional exhaustion, depersonalization, and a diminished sense of personal accomplishment [1].This review systematically evaluates the literature on the prevalence of burnout and its impact on mental health among healthcare professionals. A comprehensive search of peer-reviewed articles published between 2010 and 2023 was conducted across databases such as PubMed and PsycINFO, yielding numerous studies that provide valuable insight into this pressing issue. The selected studies highlighted various contributing factors to burnout, including excessive workload, emotional strain, and insufficient institutional support [2].Other identified factors encompass a lack of resources, inadequate staffing, and the high emotional demands associated with patient care, all of which create a challenging work environment that can lead to burnout [3]. Furthermore, the review identifies the detrimental effects of burnout on healthcare providers’ mental health and patient care outcomes, including increased errors, decreased patient satisfaction, and compromised quality of care [4]. The article also explores the cyclical nature of burnout, where providers experiencing it may become less effective, exacerbating the stress and challenges of their roles and potentially leading to even higher turnover rates within healthcare settings. Recommendations for effective interventions are discussed, emphasizing the need for institutional policies that foster a supportive work environment, promote mental well-being, and provide adequate resources for healthcare providers [5].Addressing burnout is essential for improving healthcare providers’ mental health and enhancing the quality of care delivered to patients, which is vital for healthcare systems’ overall effectiveness and sustainability.